NISP - Number of individual specimens - Romaniuk, Andrzej; Shepherd, Alexandra; Clarke, David; Sheridan, Alison; Fraser, Sheena; Bartosiewicz, László; Herman, Jeremy S. (Dryad Digital Repository, 2016)
Number of individual rodent specimens from each trench and context